2014
DOI: 10.1038/aps.2013.196
|View full text |Cite
|
Sign up to set email alerts
|

SHR3824, a novel selective inhibitor of renal sodium glucose cotransporter 2, exhibits antidiabetic efficacy in rodent models

Abstract: Aim: The sodium glucose cotransporter 2 (SGLT2) plays an important role in renal glucose reabsorption, thus serves as a new target for the treatment of diabetes. The purpose of this study was to evaluate SHR3824 as a novel selective SGLT2 inhibitor and to characterize its in vivo effects on glucose homeostasis. The effects of chronic administration of SHR3824 on peripheral insulin sensitivity and pancreatic β-cell function were also investigated. Methods: The in vitro potency and selectivity of SHR3824 were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Henagliflozin (SHR3824) is a novel, highly selective, oral inhibitor of SGLT2 12,13 . Our previous phase 2 trial (NCT02366351) showed that 12‐week treatment of henagliflozin monotherapy provided efficacious glycaemic control, reduced body weight and blood pressure, and was generally well tolerated in Chinese patients with T2D and inadequate glycaemic control with diet and exercise (data submitted for publication).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Henagliflozin (SHR3824) is a novel, highly selective, oral inhibitor of SGLT2 12,13 . Our previous phase 2 trial (NCT02366351) showed that 12‐week treatment of henagliflozin monotherapy provided efficacious glycaemic control, reduced body weight and blood pressure, and was generally well tolerated in Chinese patients with T2D and inadequate glycaemic control with diet and exercise (data submitted for publication).…”
Section: Introductionmentioning
confidence: 99%
“…3,11 Henagliflozin (SHR3824) is a novel, highly selective, oral inhibitor of SGLT2. 12,13 Our previous phase 2 trial (NCT02366351) showed that 12-week treatment of henagliflozin monotherapy provided efficacious glycaemic control, reduced body weight and blood pressure, and was generally well tolerated in Chinese patients with T2D and inadequate glycaemic control with diet and exercise (data submitted for publication). Herein, we conducted a phase 3 trial to further evaluate the efficacy and safety of henagliflozin monotherapy in this population, with results from the 24-week placebo-controlled period and additional 28-week extension period reported.…”
Section: Introductionmentioning
confidence: 99%
“…Where S′ is the substrate concentration for determining IC50 values ( Mascitti et al, 2011 ; Grempler et al, 2012 ; Yan et al, 2014 ; Cefalo et al, 2019 ; Wang et al, 2019 ; Fediuk et al, 2020 ). Km’ is the Michaelis constant of SGLT.…”
Section: Methodsmentioning
confidence: 99%
“…Henagliflozin is a novel SGLT 2 inhibitor, which has a similar structure to ertugliflozin ( Wang et al, 2016 ), and both 5 mg and 10 mg are the doses authorized for clinical use in china. Henagliflozin has an 1818-fold higher SGLT 2 selectivity as compared to SGLT transporters ( Yan et al, 2014 ). Sotagliflozin was approved for treating both T1DM and T2DM in the EU, and 200 mg or 400 mg are the doses authorized for clinical use ( He et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…3‐ n ‐Butylphthalide (NBP) [(±)‐3‐butyl‐1(3 H )‐isobenzofuranone] was firstly isolated from Chinese herbs, including Apium graveolens , Ligusticum sinensis , and Liqusticum Chuanxiong Hort , and has also been obtained by chemical synthesis . NBP is currently used clinically as a preferred drug for the treatment of ischemic stroke by increasing regional cerebral blood flow and inhibiting the release of glutamate and 5‐hydroxytryptamine . In addition, recent research has demonstrated that NBP displays beneficial effects by attenuating amyloid‐induced cell death in neuronal cultures , improving cognitive deficits and preventing neuronal cell death after focal cerebral ischemia in mice , and protecting cardiomyocytes from ischemia/reperfusion‐induced apoptosis .…”
Section: Introductionmentioning
confidence: 99%